KAJIAN KESESUAIAN EKOWISATA MANGROVE DI PANTAI BALI DESA MESJID LAMA KECAMATAN TALAWI KABUPATEN BATU BARA PROVINSI SUMATERA UTARA - Pesta Saulina Sitohang; Yunasfi Djayus; Ahmad Muhtadi Rangkuti (AQUACOASTMARINE, 2014)
Bali Beach is a located in Batu Bara with an area of approximately 637.22 ha which is a coastal area about 30.6% of the total area.This study aims to determine the potential of mangrove ecosystem for ecotourism, calculate the suitability and mangrove ecotourism carrying capacity. This research was conducted in March to April 2014. Research method used was Purposive Sampling for potential mangrove. Using three stations consisted of the first station (located at the eastern area of Bali Beach), second station (located at the middle area of Bali Beach), and the third station (located at the west coast of Bali Beach). The mangrove species found are: Excoecaria agallocha, Avicennia marina, A.lanata, Bruguiera sexangula, B.cylindrica, Rhizophora mucronata, Aegiceras corniculatum, A.Officinalis, R. stylosa, Ceriops tagal with a population density values exceeding 1000 trees / ha. Suitability index tour of mangrove is 69,23%at the first station is with under unconditional category, and at the second station and third station are 94,87% with suitability category. The carrying capacity (DDK) at first station is 12 persons/day, 37 persons/day at second station and 16 persons/day at third station.Keywords : Ecotourism, Mangrove, Bali Beach